Biochar Influences the Transformation and Translocation of Antimony in the Rhizosphere–Rice System - Qiuxiang Huang; Fande Meng; Wenzhe Chen; Yongbing Cai; Enzong Xiao (Toxics)
The rhizosphere is a crucial interface that connects the soil and the roots of plants, playing a critical role in regulating soil biochemical functions and processes. Biochar, an increasingly common soil amendment, can directly or indirectly affect the redistribution behavior of heavy metal(loid)s. Our study used a rice pot experiment to investigate the redistribution behavior of antimony (Sb) in the rhizosphere–rice system during the four key rice growth stages and analyze the effects of biochar (BC). Biochar increased pH, soil organic matter (SOM), and dissolved organic carbon (DOC) but decreased Eh, affecting Sb redistribution in the rhizosphere–rice system. The Sb fractions were altered with rice growth and the addition of BC. For example, bioavailable Sb increased by 1.57–32.97% in the presence of BC across all rice growth stages. Biochar reduced the BCF and TFR-S of Sb but elevated the TFS-G, indicating that biochar reduced Sb migration from the soil to the rice roots and the rice roots to shoots but increased Sb migration from rice shoots to grains. This study highlights the potential use of biochar as a reclamation agent in remediating Sb-contaminated soils and protecting human health from Sb through the food chain.